Pengembangan Sistem Informasi Desa Untuk Mengenalkan Potensi Dan Produk Unggulan Desa Bojong Kemang Berbasis Web Framework - Nabiyan Ali, Sulaiman; Prasetyo, Dwi Ari; Nurzatifah, Nurzatifah; Hidayat, Sarip; Ali, Ircham (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Bojong Village has great economic potential, although the economic conditions of the Bojong Village community are not the same. This is influenced by the geographical location of Bojong village, most of the Bojong village area is agricultural land. Although the majority of people in Bojong Village depend on the agricultural sector for their livelihoods, there are also people who work in other sectors such as livestock, trade, shops and MSMEs. Bojong Village is included in the category of developing villages that have a lot of potential that must be introduced or exported. The problem faced by Bojong Village, Kemang District, is that the village website is still managed by the Kemang District, so it cannot be optimal in managing and introducing all the potential that exists in Bojong Village via the website effectively, coupled with the absence of social media from Bojong Village to introduce various things. the potential that exists in digital media. Utilization of media and information systems in the form of web framework development and also improving the skills of Bojong village youth through graphic design training. The aim of implementing this program is to develop a village information system to introduce the village's potential and superior products and improve the skills of the youth of Bojong village, Kemang District, based on a web framework to the maximum. This service activity is carried out using regional observation, identification, targeting, implementation and evaluation methods.